AI-based English module needs analysis for Indonesian content creator - Prayudha; Ali, Raden Muhammad; Masduki, Anang; Alfaridhi, Dio Fahmi (Universitas Ahmad Dahlan, 2026)
The rapid growth of Indonesia’s digital economy has increased the importance of English proficiency for digital content creators. However, many digital content creators still lack the specific language skills required for global communication in this field. This study aims to identify the English language needs of digital content creators and to inform the development of an AI-based English module. A mixed-method design was employed, involving a questionnaire completed by 69 undergraduate students and interview with one English lecturer at the Collage of Multimedia (MMTC), Yogyakarta. The findings indicate that students perceive their English proficiency as moderate, with significant needs in productive skills, particularly pronunciation, speaking, and grammar for digital content task such as scripting and captioning. Students also demonstrate positive attitudes toward AI-assisted learning, especially for feedback and personalized practice, although concerns about over-reliance and ethical use remain. These results highlight the importance of integrating AI tools with authentic content creation tasks while maintaining pedagogical guidance and ethical awareness.